2016
DOI: 10.1016/j.ultrasmedbio.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Characterization of the Inferior Vena Cava in Trained and Untrained Females

Abstract: The aim of the study was to explore the long- and short-axis dimensions, shape and collapsibility of the inferior vena cava in 46 trained and 48 untrained females (mean age: 21 ± 2 y). Echocardiography in the subcostal view revealed a larger expiratory long-axis diameter (mean: 24 ± 3 vs. 20 ± 3 mm, p < 0.001) and short-axis area (mean: 5.5 ± 1.5 vs. 4.7 ± 1.4 cm, p = 0.014) in trained females. IVC shape (the ratio of short-axis major to minor diameters) and the relative decrease in IVC dimension with inspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Thus, it seems likely that differences in arterial dimension may be one factor that explains the differences between groups noted in AI. In a previous study, we found that trained females had larger inferior vena cava dimensions compared to untrained females …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, it seems likely that differences in arterial dimension may be one factor that explains the differences between groups noted in AI. In a previous study, we found that trained females had larger inferior vena cava dimensions compared to untrained females …”
Section: Discussionmentioning
confidence: 81%
“…In a previous study, we found that trained females had larger inferior vena cava dimensions compared to untrained females. 57 Based on the knowledge that hypertensive middle-aged and aged women have higher risk of developing left ventricular hypertrophy and severe heart failure than men, it has been concluded that preventive strategies directed towards earlier and more aggressive blood pressure control are especially important in women. 22 In the light of this, the present blood pressure data may provide some clues regarding the preventive potential of physical exercise in women.…”
Section: Correlations With Measures Of Arterial Distensibility and mentioning
confidence: 99%
“…All of these markers have been associated with adverse consequences of venous hypertension, both in acute and chronic settings [18][19][20][21]. However, they also all have significant limitations that may hamper their clinical usefulness when interpreted in isolation [22][23][24]. It is likely that considering a combination of these ultrasonographic features may increase the clinical usefulness of POCUS for the purpose of detecting significant venous congestion.…”
Section: Introductionmentioning
confidence: 99%
“…In the supine position, the elliptical shape of the IVC is very likely attributed to its compression from the abdominal viscera against the vertebral column; therefore, IVC diameter measurements may vary along its course during the respiratory cycle (Figure 2C). 78,79 By convention, in our practice, IVC dimensions are usually obtainable from the subcostal window when the IVC is depicted in long axis. IVC measurements are made 0.5-3.0 cm proximal to the ostium of the right atrium, while at this anatomic position, the maximal diameter (both in expiration and inspiration) is measured.…”
Section: Technical Considerations and Limitationsmentioning
confidence: 99%